Alimentos e a Química: Uma Abordagem Investigativa voltada para Estudantes Surdos - Miriã Francine dos Santos Codignola (2022)
Chemistry teaching aimed at deaf students should provide opportunities for experiences that promote interest in scientific culture and contribute to the formation of critical citizens who are co-responsible for solving everyday problems. This work aimed to develop, implement, and evaluate an Investigative Teaching Sequence (SEI) on the theme of food and its relationships with the introductory study of macronutrients for deaf students in a bilingual perspective. This research was based on a qualitative and action-research approach. Research data were collected from participant observation, recording of classes, student productions, questionnaires applied before and after the SEI, and semi-structured interview by the Sign Language Interpreter Translator (TILS). At each stage, we sought to analyze the possibilities of constructing the meanings of the following terms: carbohydrates, lipids, and proteins – based on the theme of food. The results indicated that the SEI enabled students to have a more grounded and critical argument, contributing to identifying macronutrients in daily meals and raising awareness of the importance of a balanced diet in macronutrients for the functioning of the body, promoting intellectual development and autonomy. In addition, in the classroom context, the debate on the theme of food and its chemical composition and communication in a bilingual teaching perspective mobilized processes of developing scientific concepts and promoted greater engagement of students throughout the investigative activities. Finally, this dissertation resulted in the production of the educational product entitled “A didactic sequence on carbohydrates, lipids, and proteins for deaf students”, providing chemistry teachers who teach in elementary education with a complementary material for classes on introduction to chemical composition of food for deaf students.